Mathematical Music: from Antiquity to Music AI - Braguinski, Nikita 1976- (Oxon New York Routledge, 2022)
"Mathematical Music offers a concise and easily accessible history of how mathematics was in fact used broadly to create music. The story presented in this short, engaging volume ranges from ratios in antiquity to random combinations in the 17th century, 20th-century statistics, and today's artificial intelligence. This book provides a fascinating panorama of the gradual mechanization of thought processes involved in the creation of music. How did Baroque authors envision a composition system based on combinatorics? What was it like to create musical algorithms at the beginning of the 20th century, before the computer became a reality? And how does this all explain today's use of artificial intelligence and machine learning in music? In addition to discussing the history and the present state of mathematical music, Braguinski also takes an imaginary look at what possibilities the near future of music AI might hold for listeners, musicians, and the society. Grounded in research findings from musicology and the history of technology, and written for the non-specialist general audience, this book helps the reader make sense of the discussions surrounding today's music AI by situating them in a continuous historical context"--
Composing with numbers (overview of this book) -- From continuities... Not a revolution (introduction) ; Since Antiquity ; Since the Middle Ages ; Since the Early Modern Period ; Since the 19th century ; Since 1900 ; Since 1950 -- ... to possibilities. Powerful and limited (introduction). How does deep learning work? ; Putting music AI in perspective ; Real-world music AI ; Mass-produced and still individual ; Avant-garde becomes pop's aide -- Conclusion.
Includes bibliographical references and index.
Keywords: Music history; Computer science; Mathematics; Artificial intelligence